Clinical and Biochemical Characteristics and Aetiology of Asymptomatic Raised Alanine Aminotransferase in Newly Detected Diabetes and Impaired Glucose Tolerance Patients - Rahman, Md Mahbubur; Azam, Md Golam; Ali, Md Nowshad; Mohsin, Mostafa Nur; Jamal, Md Shah; Rahim, Muhammad Abdur; Ahmed, Habib; Hoque, Md Nazmul; Buiyan, Tareq Mahmud; Rahman, Md Anisur (Journal of Bangladesh College of Physicians and Surgeons, 2016)
Objectives: Clinical evaluation and identification of aetiology of asymptomatic raised serum alanine aminotransferase (ALT) level in newly detected adult diabetic and impaired glucose tolerance (IGT) patients. Methods: In this cross-sectional study, newly detected adult diabetic and IGT patients having asymptomatic raised serum ALT level of > 1.5 times of upper limit of normal were evaluated clinically and by laboratory tests. Results: Total number of patients was 120, which was 3.1% of all newly registered diabetic and IGT patients over the study period. Male were 74 and female 46. Diabetes mellitus (DM) was found in 93.3% cases and IGT in 6.7%. Mean age was 43.1 years, mean body weight was 64.5 kg and mean body mass index (BMI) was 25.5 kg/m2. Central (abdominal) obesity was found in 61.5% cases. Increased waist hip ratio was found in 86.3% cases. Hypertension and hepatomegaly were present in 35% and 5.8% cases respectively. Dyslipidaemia was found in 98.3% cases and 45% patients fulfilled criteria for metabolic syndrome. Regarding etiology, 76.7% cases had non-alcoholic fatty liver disease (NAFLD), 8.3% had HBsAg sero-positivity, 4.2% had anti-HCV seropositivity and 3.3% had both NAFLD and HBsAg seropositivity. In 7.5% cases no cause was found. Raised serum ALT level had a significant correlation with metabolic syndrome (p= 0.016) and increasing age (p= 0.008). Conclusion: Elevation of serum ALT is common in DM and IGT. NAFLD is the commonest cause followed by hepatitis B and C virus infection. J Bangladesh Coll Phys Surg 2015; 33(2): 70-74